Digital Transformation in Retail Management: The Impact of AI Technology on Customer Experience in Physical and Online Retail (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the influence of artificial intelligence (AI) and digital transformation on customer experience (CX) within Indonesia’s retail sector, focusing on physical, online, and hybrid shopping environments. Employing a qualitative exploratory design and semi-structured interviews, the research uncovers four central themes: AI-driven personalization, the role of omnichannel integration, organizational technological readiness, and differentiation of experiences across retail channels. The findings highlight that AI facilitates superior CX primarily through real-time personalization, enabling tailored interactions that respond dynamically to customer needs. Moreover, omnichannel integration emerges as a critical mechanism that ensures a seamless and consistent customer journey across various touchpoints. The study further reveals that customer perceptions of AI-enabled services vary depending on the retail channel. Physical stores emphasize tangible interactions and human engagement, online platforms highlight efficiency and convenience, while hybrid models deliver a blend of personalized digital features and physical experience. These differences demonstrate the moderating role of channel type in shaping how customers interpret the value of AI-driven services. From a theoretical standpoint, this research extends the literature by synthesizing Service-Dominant Logic (SDL), the Technology Acceptance Model (TAM), and Omnichannel Service Integration Theory into a coherent framework for analyzing CX in digitally transformed retail environments. Practically, it provides actionable insights for retailers on designing service strategies that are transparent, customer-centric, and context-sensitive. By doing so, businesses can align emerging technologies with ethical considerations while maintaining consumer trust. Ultimately, this study underscores the importance of adaptive innovation and responsible use of AI in achieving superior, consistent, and sustainable customer experiences. In rapidly evolving retail ecosystems, balancing technological capabilities with human values is essential for delivering meaningful and competitive service encounters.